An evaluation of parking on the Kansas State University campus - Vellanki, Bharath Kumar (Kansas State University, 1994)
The rapidly increasing student enrollments, early concentrated development on inner campuses, and the wide spread growth in the use of private automobile have all combined in recent years to magnify the problems of access, circulation, and parking on the K-State campus. Kansas State University has been experiencing the problem of parking on campus since 1977. Restrictions for freshman to park on campus has created on-street parking problems and traffic congestion in residential areas within six blocks of campus. This study evaluated increasing the surface parking lots, constructing multi-level parking garages, and implementation of a shuttle system to solve the parking problem on campus. This study also considered the long range university planning goals in order to anticipate future potential sites for new buildings, possible additions to the existing buildings and/or parking structures. A feasibility analysis in terms of total costs, student share, application methodology, practical applicability to the K-State campus and impact on future campus developments are discussed.